Masyarakat Madani dalam Perspektif Hadis - Mujahid, Mujahid (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2017)
The issue of civil society or masyarakat madani has been enthusiastically discussed and associated with Islamic tradition, as the term madani itself is derived from Arabic and is regarded identical to Medina, the city in which the Prophet developed a Muslim community during his lifetime. Discussion of civil society structure becomes a choice in this description for there has been a new conception concerning the birth of a "second volume" civilized society after Medina. In fact, establishment of the concept be referred to as a "revolutionary reformation". It is indicated in the revelation of one short chapter in the Qur’an upon the Prophet’s performance of hajj wada’ (farewell pilgrimage). The verse Says "... and you see people enter the religion of Allah in droves." Elaboration on this paper is focused more on exposure to the traditions of the Prophet pertaining to the issues examined. Through the investigation conducted, it is discovered that there were many sayings and actions of the Prophet on the events of fath Makkah and hajj wada’ which led the birth of a new political order.